Canine splenic tumors: Histopathological study of 9 cases in Uruguay, 2019-2020 - Varela, Belén; Larrañaga, Camila; Yamasaki, Kanji; Verdes, José Manuel (Brazilian Journal of Veterinary Pathology, 2022)
There are no reports of what kind of spleen tumors have developed within a certain period of time in Uruguay. Therefore, we investigated spleen tumors that were surgically resected and brought into our laboratory for a year (2019-2020). As a result, 9 splenic tumors were observed. Hemangiosarcomas occurred at the highest incidence in 6 of 9 cases. In addition, 1 case each of lymphoma, fibrosarcoma, and perivascular wall tumor was observed. Furthermore, the perivascular wall tumor, which has not been reported so far, was observed in a seven years-old female Cocker Spaniel.